A quantitative assessment approach of feasible optical mechanisms contributing to structural color of golden-like Chrysina aurigans scarab beetles. (July 2015) - Azofeifa, D.E.; Hernández-Jiménez, M.; Libby, E.; Solís, A.; Barboza-Aguilar, C.; Vargas, W.E.
Abstract: Under normal incidence of non-polarized light, reflection spectra from the cuticle of golden-like C. aurigans scarabs shows a broad band displayed from 525 to 950 nm, with a spectral ripple structure that consists of a uniform sequence of peaks superimposed on the main reflection band. Cross sectional Scanning Electron Microscope (SEM) images of the cuticle initially suggest the presence of a multilayered structure. A radiative transfer matrix formalism is first applied to describe as much as possible the main features of coherent reflection spectra, by assuming optically homogenous layers distributed through the exocuticle, with chitin as the major constituent material. Additional non-coherent multiple reflections due to layers in the endocuticle are also evaluated from this approach. The presence of a pigmented micron sized structure beneath the procuticle requires the evaluation of a diffuse light contribution to the reflection. This was carried out from a four-flux radiative transfer model. Optical anisotropy is introduced by interpreting the SEM images in terms of a twisted Bouligand-type structure, and reflection spectra are evaluated from an implementation of the so-called 4×4 Berreman׳s formalism. We have been able to approach the main features characterizing the reflection spectra of C. aurigans׳ elytra following this progressive way. Highlights: Polarization of light reflected by the cuticle of C. aurigans scarabs is established. The pitch of the helical structure in the cuticle is established from SEM images. C. aurigans is a broadband natural reflector with the wider reflection band observed.